Family head versus family Members: legal issues in management of family land under yoruba customary law (2015)
The customary land tenure system is an age-long indigenous land holding system among the Yorubas of South- Western part of Nigeria. The evolution of this system and the various principles regulating same, exhibit the historical credentials rooted in the custom, value and tradition of different ethno-cultural groupings in Africa, of which the Yorubas are prominent. This paper examines the pre-colonial, colonial and post-colonial institutional structure of land ownership and management under the Yoruba native law and custom. Principally, the duties and liabilities of the head of family, principal members of the family and other members are examined vis-à-vis the role of each in the management of family land under Yoruba customary law. Causes of conflicts and conflict resolution mechanisms were equally appraised and necessary reforms suggested, such that domineering posture of some of the head of the families could be checked.